2016
DOI: 10.1111/bcpt.12609
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Lipid Emulsion as an Antidote for the Treatment of Acute Poisoning: A Bibliometric Analysis of Human and Animal Studies

Abstract: In recent years, there has been increasing interest in the role of intravenous lipid formulations as potential antidotes in patients with severe cardiotoxicity caused by drug toxicity. The aim of this study was to conduct a comprehensive bibliometric analysis of all human and animal studies featuring lipid emulsion as an antidote for the treatment of acute poisoning. The Scopus database search was performed on 5 February 2016 to analyse the research output related to intravenous lipid emulsion as an antidote f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 66 publications
2
31
0
3
Order By: Relevance
“…The number of citations for the 10 top‐cited articles in lithium toxicity varied from 211 to 79, which was less than those in other subspecialties in non‐toxicological fields and within the range of citations in other subspecialties in toxicological fields . Citations fluctuate in different subspecialties and depend on the research activity in certain field.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The number of citations for the 10 top‐cited articles in lithium toxicity varied from 211 to 79, which was less than those in other subspecialties in non‐toxicological fields and within the range of citations in other subspecialties in toxicological fields . Citations fluctuate in different subspecialties and depend on the research activity in certain field.…”
Section: Discussionmentioning
confidence: 97%
“…The USA and the UK were the most influential countries with the most publications, productive institutions and international cooperation. Bibliometric studies in other toxicological fields also demonstrated the predominance of the USA and the UK over other worldwide countries in number and quality of research output in various toxicological fields . This research activity in the field of lithium toxicity may be related to population size, economic factors, the size of the scientific community, research traditions and funding in these countries , and also the incidence of lithium toxicity or number of poison centres may play a role in research performance .…”
Section: Discussionmentioning
confidence: 99%
“…The methodology applied in this study was comparable to recent bibliometric studies [17,[31][32][33][34][35]. This study was focused on identifying WNV publication trends with regard to publication year, publication type, prolific countries, language of publication, as well as, prolific journals, citations, and collaboration patterns.…”
Section: Methodsmentioning
confidence: 99%
“…Data collection for this study was carried out using Scopus database. The methodology used was similar to that described in previously published bibliometric studies [15][16][17][18][19][20][21]. Keywords used for data extraction were obtained from published review articles on carbapenem resistance.…”
Section: Methodsmentioning
confidence: 99%